2018
DOI: 10.1186/s40409-018-0144-0
|View full text |Cite
|
Sign up to set email alerts
|

Antivenom therapy: efficacy of premedication for the prevention of adverse reactions

Abstract: Antivenoms or antitoxins have been effectively used for more than a century. During this time, these products have always proven to be highly effective in the treatment of infections and envenomations. However, antivenoms did not exhibit good safety results in their initial applications. After many improvements, antivenoms have substantially better safety profiles but still have some side effects. Due to the occurrence of adverse reactions, the practice of using premedication with the intent to decrease side e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 35 publications
2
28
0
1
Order By: Relevance
“…Adverse reactions to antivenom may be early or late developing due to the involvement of different pathological pathways, including early developing IgE anaphylaxis, early developing non-IgE-mediated anaphylactoid reactions, and the IgG and IgM mediated late developing adverse reaction of serum sickness [ 49 , 145 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 ]. However, premedication with adrenalin has been shown to significantly reduce the incidence of early adverse reactions [ 193 , 199 , 200 , 201 , 202 , 203 ]. One study resulted in the contrary conclusion that adrenalin was not effective since 2 out of 11 (18%) patients receiving adrenalin had allergic responses while 20 out of 86 (23%) not receiving any form of premedication developed allergic responses [ 204 ].…”
Section: Issues and Controversies In Modern Medical Carementioning
confidence: 99%
“…Adverse reactions to antivenom may be early or late developing due to the involvement of different pathological pathways, including early developing IgE anaphylaxis, early developing non-IgE-mediated anaphylactoid reactions, and the IgG and IgM mediated late developing adverse reaction of serum sickness [ 49 , 145 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 ]. However, premedication with adrenalin has been shown to significantly reduce the incidence of early adverse reactions [ 193 , 199 , 200 , 201 , 202 , 203 ]. One study resulted in the contrary conclusion that adrenalin was not effective since 2 out of 11 (18%) patients receiving adrenalin had allergic responses while 20 out of 86 (23%) not receiving any form of premedication developed allergic responses [ 204 ].…”
Section: Issues and Controversies In Modern Medical Carementioning
confidence: 99%
“…This leads to difficulty in administering the correct antivenom, especially in those patients with significant coagulopathy. Although the concurrent use of two specific antivenoms may be practiced clinically, the high cost in generating antivenom, low inventory, and its side effects, such as serum sickness, should also be considered [1821]. The correct clinical differential diagnosis between these two types of snakebites is paramount.…”
Section: Introductionmentioning
confidence: 99%
“…Non-IgE-mediated anaphylactic reactions constitute the majority of early reactions induced by therapeutic immunoglobulins. In theory, removal of the Fc portion of IgG could prevent these reactions [ 10 ]. However, various studies have shown that both IgG or F(ab’) 2 heterologous immunoglobulins can activate the complement system in vitro [ 11 , 12 ], and protein concentration and aggregation has been increasingly suggested to be the major cause of serum therapy early reactions [ 13 – 15 ].…”
Section: Introductionmentioning
confidence: 99%